2017
DOI: 10.1001/jamaneurol.2017.1460
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Examination in Survivors of Ebola Virus Disease

Abstract: Role of the Funder/Sponsor: The funding sources had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…EBOV infection of the supporting cells of the peripheral ganglia and nerves, with attendant inflammation, is intriguing, as the nature of neurologic impairment in EVD survivors is hotly debated 17 , 26 , 44 , 45 . Damage to these neural supporting cells, with a pro-inflammatory resolution, could conceivably lead to long-term nerve or ganglion damage, manifesting as altered sensory inputs or dysautonomia.…”
Section: Discussionmentioning
confidence: 99%
“…EBOV infection of the supporting cells of the peripheral ganglia and nerves, with attendant inflammation, is intriguing, as the nature of neurologic impairment in EVD survivors is hotly debated 17 , 26 , 44 , 45 . Damage to these neural supporting cells, with a pro-inflammatory resolution, could conceivably lead to long-term nerve or ganglion damage, manifesting as altered sensory inputs or dysautonomia.…”
Section: Discussionmentioning
confidence: 99%
“…The observations in this study on the detection of HTLV-1 viral antigens in exosomes found in virus-free CSF supernatant has implications for other virally associated neuroinflammatory diseases. For example, Ebola virus has been shown to be associated with long-term neurologic sequelae even though the virus is thought to have been cleared [ 81 , 82 ], and while Ebola viral proteins have been detected within exosomes in vitro [ 83 ], this has not yet been shown to be the case within patient CSF material. As we have demonstrated that HAM/TSP CSF supernatant, which is HTLV-1 negative, contains HTLV-1 Tax + exosomes, exosomes containing viral antigens could be a potential biomarker for neurologic disorders associated with viral infections in which the virus may be absent in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of common neurological sequelae in survivors of recent filovirus outbreaks has reignited the debate about whether these observed clinical signs are a direct result of neuronal infection or are a by-product of antiviral immune responses. The demonstration of infectious virus in the CSF of patients is a clear indication that the virus is capable of entering and replicating within the immunoprivileged locale of the CNS (8, 15, 21). The demonstration of viral persistence in other immunoprivileged sites, such as the eye and testes, also raises the question of viral persistence in the CNS (23, 26, 50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to the initial Marburg virus outbreaks, most symptomatic human filovirus infections occurred in remote communities in Africa, in countries without efficient medical infrastructure and a small number of survivors with minimal opportunities for follow-up. A recent large-scale Ebola virus outbreak in West Africa has permitted the tracing of survivors and have allowed for the determination of longer-term effects of Ebola virus infection in humans (820). These long-term sequelae include a range of neurological and psychological disorders, including headache, fatigue, depression, meningoencephalitis, and cerebral and/or cerebella atrophy (810, 12–17, 19, 20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation